Design and development of split-parallel through-the road retrofit hybrid electric vehicle with in-wheel motors - Zulkifli, S.A. (Institute of Physics Publishing, 2015)
One configuration of the hybrid electric vehicle (HEV) is the split-axle parallel hybrid, in which an internal combustion engine (ICE) and an electric motor provide propulsion power to different axles. A particular sub-type of the split-parallel hybrid does not have the electric motor installed on board the vehicle; instead, two electric motors are placed in the hubs of the non-driven wheels, called 'hub motor' or 'in-wheel motor' (IWM). Since propulsion power from the ICE and IWM is coupled through the vehicle itself, its wheels and the road on which it moves, this particular configuration is termed 'through-the-road' (TTR) hybrid. TTR configuration enables existing ICE-powered vehicles to be retrofitted into an HEV with minimal physical modification. This work describes design of a retrofit-conversion TTR-IWM hybrid vehicle - its sub-systems and development work. Operating modes and power flow of the TTR hybrid, its torque coupling and resultant traction profiles are initially discussed.